Crop waste management proposal in rice systems at the department of Cordoba, Colombia - Urrea-Ceferino, Gloria; Grimaldos Mojica, Manuel Alejandro (Economia agro-alimentare/Food Economy - Open Access, 2023)
The claim for food increases with the waste caused by its production. Rice is appetized but the agro-industrial residue, such as straw and husk, becomes a problem when they’re not properly managed. However, renewable source demands grew, indeed, the chains of rice residue as cellulose, lignin, hemicellulose, carbon, and silica could be transformed into: fuel, power generation, gas production, paper manufactory, and fertilizer for the production of fungi and building material. The industrial implementation of rice residue management worldwide has a lack. In this case, it was observed more closely the rice cultivation in a local region of Colombia. The aim of this research was to present the current market, challenges and the proposal of a proper management residue on a circular economy incorporated into Córdoba department rice market. The study was conducted through scientific and comprehensive insights on rice crop waste management options. The selection criteria of the articles were rice production, major components of rice paddy, straw, and husks, and waste disposal in rice systems. Farmers, researchers, federations, administration, and management, need to work on, improving the nutrients of the soil, the quality of the crop, and the management of the residue, the one that remains in the mills and the one that remains in the fields. Finally, in all processes, the required investment to obtain a product that meets current market requirements on renewable fuels or raw materials.